LiDAR-driven Topographic Surveys for Floodplain Management - E. S. Malinverni; F. Di Stefano; S. Chiappini; G. Darvini; D. Fronzi; R. Pierdicca; A. Tazioli (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
LiDAR technology has become an essential tool for hydrological monitoring, offering high-resolution topographic data for river basin management. This study presents LiDAR-based topographic surveys conducted on the Metauro and Cesano river basins in Central Italy to improve flood risk assessment and regional planning. Airborne LiDAR and ground-based GNSS techniques have been integrated to generate accurate DTMs and DSMs, enabling precise floodplain mapping and man-made structures analysis. The data processing involved automated classification and manual corrections to differentiate between terrain, vegetation, and built structures. The results provided detailed cross-sectional altimetric profiles, revealing geomorphological changes such as sediment deposition and erosion. Additionally, Airborne LiDAR-derived datasets supported flood modeling, infrastructure assessment, and long-term environmental monitoring. The study highlights the effectiveness of LiDAR data collection in hydrological management, enhancing flood risk mitigation, urban planning, and ecological restoration. Future research should focus on expanding survey coverage, integrating real-time flood forecasting, and leveraging AI-driven techniques for automated data processing. This work contributes to improved geospatial knowledge, providing decision-makers with advanced tools for sustainable surface water resource management.